Airbag Pneumonitis - Raghav Govindarajan; Gustavo Ferrer; Laurence A. Smolley; Eduardo Araujo Oliveira; Franck Rahaghi (Case Reports in Medicine)
The widespread and mandatory use of airbags has resulted in various patterns of injuries and complications unique to their use. Airbags have been implicated in a spectrum of pulmonary conditions ranging from exacerbation of asthma, reactive airway diseases to new onset asthma. We report a case of inhalational chemical pneumonitis that developed after exposure to the airbag fumes.